Quasi‐2D Perovskites: Controlling Spatial Crystallization Uniformity and Phase Orientation of Quasi‐2D Perovskite‐Based Light‐Emitting Diodes Using Lewis Bases (Adv. Mater. Interfaces 2/2020). Issue 3 (7th February 2020) - Han, Yaeeun; Park, Sungbin; Wang, Jian; Jariwala, Sarthak; Lee, Kangmin; Bischak, Connor G.; Kim, Sohyeon; Hong, Jungyun; Kim, Sunwoo; Lee, Mi Jung; Ginger, David S.; Hwang, Inchan
Abstract : The stability of intermediate complexes formed by the addition of Lewis bases is a key factor in modulating orientation of quasi‐2D perovskites as well as enhancing spatial uniformity of crystallization. Random orientation benefits the device performance of light‐emitting diodes. More details can be found in article number 1901860 by Yaeeun Han, Inchan Hwang, and co‐workers.